PpeTAC1 promotes the horizontal growth of branches in peach trees and is a member of a functionally conserved gene family found in diverse plants species. (13th June 2013) - Dardick, Chris; Callahan, Ann; Horn, Renate; Ruiz, Karina B.; Zhebentyayeva, Tetyana; Hollender, Courtney; Whitaker, Michael; Abbott, Albert; Scorza, Ralph
Summary: Trees are capable of tremendous architectural plasticity, allowing them to maximize their light exposure under highly competitive environments. One key component of tree architecture is the branch angle, yet little is known about the molecular basis for the spatial patterning of branches in trees. Here, we report the identification of a candidate gene for the br mutation in Prunus persica (peach) associated with vertically oriented growth of branches, referred to as 'pillar' or 'broomy'. Ppa010082, annotated as hypothetical protein in the peach genome sequence, was identified as a candidate gene for br using a next generation sequence‐based mapping approach. Sequence similarity searches identified rice TAC1 ( tiller angle control 1 ) as a putative ortholog, and we thus named it PpeTAC1 . In monocots, TAC1 is known to lead to less compact growth by increasing the tiller angle. In Arabidopsis, an attac1 mutant showed more vertical branch growth angles, suggesting that the gene functions universally to promote the horizontal growth of branches. TAC1 genes belong to a gene family (here named IGT for a shared conserved motif) found in all plant genomes, consisting of two clades: one containing TAC1 ‐like genes; the other containing LAZY1, which contains an EAR motif, and promotes vertical shoot growth in Oryza sativa (rice) and Arabidopsis through influencing polar auxin transport. The data suggest that IGT genes are ancient, and play conserved roles in determining shoot growth angles in plants. Understanding how IGT genes modulate branch angles will provide insights into how different architectural growth habits evolved in terrestrial plants.